The chording glove: a glove-based text input device - Rosenberg, R.; Slater, M. (IEEE transactions on systems, man and cybernetics. Part C, Applications and reviews, 1999)
This paper introduces a new text input device called the chording glove. The keys of a chord keyboard are mounted on the fingers of a glove. A chord can be made by pressing the fingers against any surface. Shift buttons placed on the index finger enable the glove to enter the full ASCII character set. The chording glove is designed as a text input device for wearable computers and virtual environments. An experiment was conducted to assess the performance of the glove. After an average of 80 min of a tutorial, ten subjects reached a continuous text input speed of 8.9/spl plusmn/1.4 words/min, and after 10 1-hr sessions, they achieved 16.8/spl plusmn/2.5 words/min.